Influence of altitude training modality on performance and total haemoglobin mass in elite swimmers - Gough, C. E.; Saunders, P. U.; Fowlie, J.; Savage, B.; Pyne, D. B.; Anson, J. M.; Wachsmuth, N.; Prommer, N.; Gore, C. J. (European Journal of Applied Physiology, 2012)
We compared changes in performance and total haemoglobin mass (tHb) of elite swimmers in the weeks following either Classic or Live High:Train Low (LHTL) altitude training. Twenty-six elite swimmers (15 male, 11 female, 21.4 ± 2.7 years; mean ± SD) were divided into two groups for 3 weeks of either Classic or LHTL altitude training. Swimming performances over 100 or 200 m were assessed before altitude, then 1, 7, 14 and 28 days after returning to sea-level. Total haemoglobin mass was measured twice before altitude, then 1 and 14 days after return to sea-level. Changes in swimming performance in the first week after Classic and LHTL were compared against those of Race Control (n = 11), a group of elite swimmers who did not complete altitude training. In addition, a season-long comparison of swimming performance between altitude and non-altitude groups was undertaken to compare the progression of performances over the course of a competitive season. Regardless of altitude training modality, swimming performances were substantially slower 1 day (Classic 1.4 ± 1.3% and LHTL 1.6 ± 1.6%; mean ± 90% confidence limits) and 7 days (0.9 ± 1.0% and 1.9 ± 1.1%) after altitude compared to Race Control. In both groups, performances 14 and 28 days after altitude were not different from pre-altitude. The season-long comparison indicated that no clear advantage was obtained by swimmers who completed altitude training. Both Classic and LHTL elicited ~4% increases in tHb. Although altitude training induced erythropoeisis, this physiological adaptation did not transfer directly into improved competitive performance in elite swimmers.